Avaliação de programa de gerenciamento de uso de antimicrobianos - Pagnussat, Lidiane Riva (2019)
Antibiotic Stewardship Program are important to improve management and optimize antimicrobial therapy. Knowing the reality of each institution becomes fundamental to identify fragile points and collaborate to build new strategies. Our objective was to evaluate the activities performed by a PGA. We performed an observational, prospective and analytical study in a large hospital, high complexity and teaching, from August to September 2018. Patients were included in antimicrobial use for a period of 24 hours or more and whose prescriptions were evaluated by the PGA. We evaluated 637 antimicrobial prescriptions and identified 171 interventions. The main intervention was the suspension of the prescribed antimicrobial 35%. Adherence of prescribers occurred in 121 cases, which corresponds to an adhesion rate of 74.7%. Adhering to interventions suggested by the PGA did not have a significant impact on mortality, length of stay and growth of multiresistant microorganisms, but had a significant impact on the mean time of antimicrobial use (p = 0.007), on the days of therapy per 1,000 patient-days ( p = 0.002) and on the days that the patients remained without antimicrobial (p = 0.001). We observed a real savings of R$ 101,854.93 and the institution stopped using 216 days of antimicrobials. The simulation showed that the economic impact could be even greater by adding R$ 210,031.21 and 287 days without antimicrobial. The adhesion rate was good, above the average of the literature. The significant impact on consumption, the number of days the institution stopped using antimicrobials, and actual cost reduction demonstrate the effectiveness and consolidation of an PGA and the simulation of an ideal program shows opportunities for improvement and may justify continued administrative support to activities carried out by the PGA.